2012
DOI: 10.1117/1.jbo.17.12.125001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change of collateral flow varying with distribution of regional blood flow in acute ischemic rat cortex

Abstract: Cerebral blood flow (CBF) is critical for the maintenance of cerebral function by guaranteed constant oxygen and glucose supply to brain. Collateral channels (CCs) are recruited to provide alternatives to CBF to ischemic regions once the primary vessel is occluded during ischemic stroke. However, the knowledge of the relationship between dynamic evolution of collateral flow and the distribution of regional blood flow remains limited. In this study, laser speckle imaging was used to assess dynamic changes of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…It is therefore desirable to use a non-invasive in vivo imaging technology to study the process of arteriogenesis. Laser speckle perfusion imaging (LSI) has been explored to reveal the dynamic change in the cortical collateral circulation in rodent models during acute ischemic stroke (Wang, et al, 2012). However, the spatial resolution of LSI is inadequate to visualize the detailed collateral remodeling of small vessels within localized regions.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore desirable to use a non-invasive in vivo imaging technology to study the process of arteriogenesis. Laser speckle perfusion imaging (LSI) has been explored to reveal the dynamic change in the cortical collateral circulation in rodent models during acute ischemic stroke (Wang, et al, 2012). However, the spatial resolution of LSI is inadequate to visualize the detailed collateral remodeling of small vessels within localized regions.…”
Section: Introductionmentioning
confidence: 99%
“…7,[16][17][18][19][20][21] The degree of retrograde flow is proportional to regional cerebral blood flow within the MCA territory. 19 In…”
Section: Experimental Strokementioning
confidence: 99%
“…7,16 Second, collaterals represent a subsidiary vascular network able to provide retrograde perfusion to the ischemic territory during major vessel occlusion. [16][17][18][19] Collateral blood flow changes from bidirectional to unidirectional, toward the occluded arterial territory (MCA), and increases in velocity. 7,[16][17][18][19][20][21] The degree of retrograde flow is proportional to regional cerebral blood flow within the MCA territory.…”
Section: Experimental Strokementioning
confidence: 99%
“…Analogous to rat studies, the recruited collaterals evaluated in our study were persistent rather than impermanent or transient. 12 In animal studies, if this subacute response resulted in hyperperfusion at day 4, it was associated with a larger final infarct size as compared to animals with maximal hyperperfusion at day 1. 23 Our study shows that collateral recruitment on the day 2 scan per se is an independent predictor of higher mortality, but not functional outcomes.…”
mentioning
confidence: 99%
“…In rat studies, 3 different types of collaterals have been identified: transient collaterals that could be seen immediately after the stroke and last less than 90 minutes; impermanent collaterals that disappear after 90-150 minutes; and persistent collaterals, which can be seen for longer periods. 12 There is a dearth of literature on the temporal evolution of leptomeningeal collaterals in AIS in humans. Perhaps this is due to the emergent nature of AIS, which is not conducive to serial imaging required for elucidating this phenomenon.…”
mentioning
confidence: 99%